The Effect of Part-Time Work on Learning Activities and Academic Achievement - Ikromatus Sakdiyeh; Ruski Ruski; Subandy Widjaya (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research was conducted to determine the Influence of Part-Time Work on Learning Activities and Academic Achievement of the 2019 cohort of students at STKIP PGRI Bangkalan. The independent variable in this research is part-time work, while the dependent variables are learning activity and academic achievement. The population for this study consists of all undergraduate education students from the 2019 cohort at STKIP PGRI Bangkalan, totaling 246 individuals, regardless of their part-time work status. The sample for this research includes the entire population, and the sampling technique employed is proportionate stratified random sampling, where all individuals in the population have an equal chance of being selected as sample members. Data collection techniques used include questionnaires and documentation. The analysis technique employed is MANOVA (Multivariate Analysis of Variance). The results of the research indicate that part-time work influences the variable of student learning activity, as the part-time work variable shows a positive effect, with a significance value of 0.009 (p < 0.05) and tcount > ttable (2.788 > 2.045). Therefore, the null hypothesis (HO) is rejected, and the alternative hypothesis (HI) is accepted. Furthermore, part-time work also affects the variable of student academic achievement, as the part-time work variable has a positive effect, with a significance value of 0.023 (p < 0.05) and tcount > ttable (2.397 > 2.045). Hence, the null hypothesis (HO) is rejected, and the alternative hypothesis (HI) is accepted.